2020
DOI: 10.1111/add.15269
|View full text |Cite
|
Sign up to set email alerts
|

England SimSmoke: the impact of nicotine vaping on smoking prevalence and smoking‐attributable deaths in England

Abstract: Background and Aims Whereas the use of nicotine vaping products (NVPs) is widespread, their impact on smoking prevalence is controversial. This study considered the potential impact of NVPs on smoking prevalence in England. Design Indirect simulation model. The England SimSmoke model is validated through 2012, before NVP use became more widely used by smokers. Because information on NVP‐related transitions is limited, an indirect method is used; the difference in observed smoking prevalence (reflecting NVPs) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 63 publications
2
15
0
1
Order By: Relevance
“…Our findings for all US adults are similar to those from the England SimSmoke model that applied the same methodology [78]. We obtained reductions of 14-20% for males and 13-20% for females from 2012 to 2018.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings for all US adults are similar to those from the England SimSmoke model that applied the same methodology [78]. We obtained reductions of 14-20% for males and 13-20% for females from 2012 to 2018.…”
Section: Discussionsupporting
confidence: 83%
“…65 Consistent with these population studies, simulation analyses have generally found that vaping increases smoking cessation, avoiding large numbers of premature deaths. [66][67][68][69] Other researchers have found regular and frequent e-cigarette use to be associated with increased smoking cessation, while infrequent use was not. 70 -75 This could reflect self-selection, with frequent vapers possibly liking vaping more and being more motivated to quit smoking.…”
Section: Population Studiesmentioning
confidence: 99%
“…Similarly, in the study by Walker et al [2], all measures of e-cigarette use increased and all measures of tobacco use decreased or remained stable over the 2014-2019 period among New Zealand youth aged 14-15 years. Lastly, in the UK, the substantial reduction in smoking prevalence in the adult population was found to coincide with a rise in e-cigarette use between 2012 and 2019 [14]. The upward trend in e-cigarette experimentation and use may be partly explained by the gradual progression from smoking to vaping in the general population, a shift in behaviour actually recommended by bodies such as Public Health England and the French National Academy of Medicine.…”
Section: Discussionmentioning
confidence: 92%
“…Three Cochrane reviews nd that nicotine e-cigarettes are more effective than nicotine substitutes in helping young adult smokers wean themselves off smoking [10][11][12]. In the UK, the 2021 Public Health England report [13] concludes that e-cigarettes are an effective aid to smoking cessation and reduction, while Levy et al [14] suggest that the observed reduction in smoking prevalence in the adult population is explained by the increased use of nicotine ecigarettes. In France, Legleye et al [15] report a 42% reduction in the risk of becoming a daily smoker in adolescents aged [17][18].5 years who experimented with e-cigarettes rst, and Chyderiotis et al [16] [15] con rm the absence of an increased risk of progression from vaping to daily smoking among adolescents aged 17 years.…”
Section: Introductionmentioning
confidence: 99%